Immune Response and Prognosis of Chronic Kidney Disease Patients Undergoing Hemodialysis Against COVID-19: A Systematic Review - Nurul Hanifa; Riri Andri Muzasti (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Chronic kidney disease (CKD) patients are characterized by immune response dysfunction which increased susceptibility to infections. CKD is one of the Coronavirus disease-2019 (COVID-19) comorbidity that generally has a poor clinical outcome and patients undergoing hemodialysis had a 50% hospitalization rate and 20%-30% mortality rate. Seroconversion after confirmation of COVID-19 infection is close to 100% in the dialysis population, but the durability of the immune response and the extent as a protection against infection remains unclear. This study aimed to determine the immune response and prognosis of CKD patients undergoing hemodialysis against COVID-19.Objective: To determine immune response and prognosis of CKD patients undergoing hemodialysis against COVID-19.Methods: This is a systematic review study that used literature sourced from online journal databases on Google Scholar, PubMed, Cochrane, and Clinical Key sites. Literature that has passed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) staging and the journal quality review based on the Newcastle-Ottawa Scale (NOS) assessment is then synthesized qualitatively and presented systematically.Results: Based on the data analysis, there were positive immune responses in 460 of 735 (62.6%) CKD patients undergoing hemodialysis against COVID-19 and a higher mortality rate (10.5%) than the control group (6.9%).Conclusion: The immune response and prognosis of CKD patients undergoing hemodialysis against COVID-19 were worse than the control group. Therefore, COVID-19 vaccination should be prioritized in CKD patients undergoing hemodialysis.